104 Management of sports-related concussion in UK emergency departments: a multi-centre study. Issue 12 (23rd November 2020) - Rashid, Haroon; Dobbin, Nick; Mishra, Smarak
Abstract : Aims/Objectives/Background: It is necessary for those working in emergency departments to have adequate knowledge and delivery of current sport-related concussion (SRC) management protocols including identifying patients with concussion, managing their symptoms, giving appropriate advice with regards to return to play and referring those at risk of further injuries to an appropriate service. This study aimed to establish the current practice, knowledge base and views towards SRC management of emergency department clinicians who have trained or are currently training in emergency medicine in the North West of England. Methods/Design: This study was a multi centre, cross sectional study of 111 emergency department clinicians (EDCs) working across 15 centres in the North West of England A 21 item online survey was issued. The key questions focused on the advice given to patients on discharge, the importance of cognitive and physical rest, and knowledge of GRTP. Results/Conclusions: Approximately, 37% of the population responded to the invitation, with 111 responses included in this study. Only 27% of total respondents were aware of the Consensus Statements of Concussion in Sport guidelines, whilst 45% were unaware of any SRC guidelines. 57% of respondents had heard of a graded return to play (GRTP) protocol. Physical rest following an SRC was advised by 95% of respondents with 61% advising concomitant cognitive rest and 42% of respondents providing specific written advice. 90% of clinicians had not received any SRC training. There is a lack of knowledge amongst EDCs in the North West of England in managing and providing discharge advice according to recommendations for patients with SRC. This is likely a consequence of the limited training that these clinicians have received in managing SRC and suggests further work needs to be undertaken to educate EDCs on current SRC management guidance to ensure appropriate care and discharge advice is given to patients.